2010
DOI: 10.1002/bin.301
|View full text |Cite
|
Sign up to set email alerts
|

Training and testing music skills in a boy with autism using a matching‐to‐sample format

Abstract: A 16-year old boy with autism was taught music skills using a matching to sample procedure. He was trained and subsequently tested for the formation of four 4-member classes, including different visual music stimuli, and Norwegian and Vietnamese labels for different major and minor chords. Four different stimuli sets were trained both in one-to-many (OTM) and many-to-one (MTO) training structures. Further, we explored if the reaction times to comparison stimuli increased from training to testing. Results showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
23
0
7

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 20 publications
2
23
0
7
Order By: Relevance
“…A number of studies have demonstrated the success of MTS to establish skills such as identity matching (de Alcantara Gil, de Oliveira, & McIlvane, ; Fisher et al ), spelling and letter recognition (Lane & Critchfield, ; Stromer, Mackay, Howell, McVay, & Flusser, ), money (Keintz, Miguel, Kao, & Finn, ), music (e.g., Artnzen, Halstadtro, Bjerke, & Halstadtro, ), geography (e.g., LeBlanc, Miguel, Cummings, Goldsmith, & Carr, ), etc. Successful MTS responding, however, may be difficult for individuals who lack necessary prerequisite skills for accurate conditional discrimination learning (Green, ; Grow, Carr, Kodak, Jostad, & Kisamore, ; McIlvane, Dube, Kledaras, Iennaco, & Stoddard, ).…”
mentioning
confidence: 99%
“…A number of studies have demonstrated the success of MTS to establish skills such as identity matching (de Alcantara Gil, de Oliveira, & McIlvane, ; Fisher et al ), spelling and letter recognition (Lane & Critchfield, ; Stromer, Mackay, Howell, McVay, & Flusser, ), money (Keintz, Miguel, Kao, & Finn, ), music (e.g., Artnzen, Halstadtro, Bjerke, & Halstadtro, ), geography (e.g., LeBlanc, Miguel, Cummings, Goldsmith, & Carr, ), etc. Successful MTS responding, however, may be difficult for individuals who lack necessary prerequisite skills for accurate conditional discrimination learning (Green, ; Grow, Carr, Kodak, Jostad, & Kisamore, ; McIlvane, Dube, Kledaras, Iennaco, & Stoddard, ).…”
mentioning
confidence: 99%
“…More recently, EBI has been expanded to teach college students statistics, neuroanatomy, prescription drug names, and even single‐subject research design (e.g., Albright, Reeve, Reeve, & Kisamore, ; Fienup, Wright, & Fields, ; Walker & Rehfeldt, ; Zinn, Newland, & Ritchie, ). Nevertheless, a limited number of EBI studies have been conducted on leisure skills, including musical education (Arntzen, Halstadtro, Bjerke, & Halstadtro, 2010; Hayes, Thompson, & Hayes, ; Perez & de Rose, ). This is surprising considering that note reading and music playing skills have been correlated with improved reading and math performance, higher overall IQ, and increased social awareness (e.g., Graziano, Peterson, & Shaw, ; Kaviani, Mirbaha, Pournaseh, & Sagan, ; Long, ; Sussman, ).…”
mentioning
confidence: 99%
“…Esse é o caso do presente estudo, em que foram estabelecidas relações de linha de base para a formação de sete classes com três estímulos cada. Cabe destacar, no entanto, que no estudo de Arntzen et al (2010), em que quatro classes com quatro membros foram estabelecidas, a estrutura SaN foi mais efetiva na produção de relações emergentes.…”
Section: Discussionunclassified
“…O procedimento para alcançar esses objetivos difere dos procedimentos descritos anteriormente (Arntzen et al, 2010;Filgueiras, 2011;Hayes et al 1989;Pereira, 2012) …”
Section: Procedimentounclassified
See 1 more Smart Citation